Students’, Pre-Service Mathematics Teachers’, and In-Service Mathematics Teachers’ Perception on Calculus Learning Video - Shelly Lubis; Wahyu Setyaningrum; Abdul Halim Abdullah; Muhamad Rizky Al Gafari; Habibullah Habibullah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
Calculus is a branch of mathematics that must be studied in school, especially at the high school level. One of the subjects in calculus is the application of integral on the volume of solid of revolution. The use of learning video as media can help students in a conceptual understanding of the volume of solid of revolution, which is one of the abstract objects in calculus. This article discusses the development of solid revolution learning videos' volume. It describes students' perception, pre-service mathematics teachers, and in-service mathematics teachers in the video. The subjects who participated in this study were 48 students in grade 12 in one state high school in Sambas Regency, West Borneo, 8 pre-service mathematics teachers of one of the universities in Yogyakarta, and 3 high school mathematics teachers in Sambas Regency. Data were collected by using a questionnaire consisting of several open questions. Through open questions, subjects were intended to express their ideas or opinions about the learning video. The finding showed that most respondents have positive perceptions of calculus learning video. 76,74% of students agree that the video is suitable for use at the beginning of learning this subject; all in-service mathematics teachers agree, and 75% of pre-service mathematics teachers also agree. This indicates that the learning video can be used as one of the teaching aids in the learning of solid revolution